Search for the Standard Model Higgs boson in the decay channel H -> ZZ(()*()) -> 4l with the ATLAS detector - Aad, G; Abbott, B; Abdallah, J; Abdelalim, A; Abdesselam, A; Abdinov, O; Abi, B; Abolin, M; Abramowicz, H; Abreu, H; Acerbi, E; Acharya, B; et al. (2011)
A search for the Standard Model Higgs boson in the decay channel H→ZZ(*)→ℓ+ℓ-ℓ'+ℓ'-, where ℓ=e, μ, is presented. Proton-proton collision data at s=7TeV recorded with the ATLAS detector and corresponding to an average integrated luminosity of 2.1fb-1 are compared to the Standard Model expectations. Upper limits on the production cross section of a Standard Model Higgs boson with a mass between 110 and 600GeV are derived. The observed (expected) 95% confidence level upper limit on the production cross section for a Higgs boson with a mass of 194 GeV, the region with the best expected sensitivity for this search, is 0.99 (1.01) times the Standard Model prediction. The Standard Model Higgs boson is excluded at 95% confidence level in the mass ranges 191-197, 199-200 and 214-224 GeV. © 2011 CERN.